Emergent consilience among coeval fishing and farming communities of the middle holocene on the North Peruvian coast - Dillehay, Tom D.; Tham, Teresa Rosales; Vázquez, Victor; Goodbred, Steve; Chamberlain, Elizabeth; Rodríguez, Gabino (Frontiers in Earth Science, 2022)
Coasts are dynamic, constantly changing ecosystems offering rich and varied foods and other resources. Compared with the monistic structure of crop production in many terrestrial parts of the world, some coastlines reflect a dualistic structure with complementary maritime and agricultural economies beginning in early prehistoric times. In particular, the Pacific coast of the Central Andes offers one of the world’s most abundant and diverse supplies of marine resources. The late Pleistocene to middle Holocene (∼14,500–4,000 BP) cultural sequences from south Ecuador to north Chile vary appreciably from one region to the next, but all reveal varying degrees of mixed diets of maritime and terrestrial foods. By at least ∼7,000 BP, a diversity of seafood and domesticated crops were mutually exchanged to form varied specialized and unspecialized economies in a few Andean areas. This study reports on interdisciplinary data from a complex of archaeological sites with mixed economies along the desert coast of the Chicama Valley in north Peru, specifically the Huaca Prieta area dating between ∼14,500 and 3,800 BP. Around 7,500–7,000 BP, intensified maritime and agriculture economies developed simultaneously with social differentiation between public ritual monuments and outlying domestic support sites in an environment of rich marine resources and fertile estuarine wetlands in the valley. This and other coastal areas played an important and persistent early role in human population growth, community formation, and the consilience of different but complementary technologies and principles of socio-economic organization to establish the foundations for later state development along the Central Andean coast.